Analisis Penerimaan Aplikasi Kopi Kenangan Menggunakan Metode Technology Acceptance Model - Byanca Rebecca Yocelyn Sitompul; Anisah Herian (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to analyze user acceptance of the Kopi Kenangan Application using the Technology Acceptance Model method. A questionnaire was used to collect data, including variables evaluating perceived usefulness, perceived ease of use, and attitude toward use. A total of 100 people took part in the research. Data acquired via questionnaires were validated and reliable before being analyzed using multiple linear regression techniques. The results of the first regression equation analysis demonstrate that the variable Perceived Usefulness has a significant impact on the variable Attitude toward Using, with a t count of 10.322 and a significance of p = 0.001(<0.05). The variable Perceived Ease of Use has a significant impact on the variable Attitude toward Using as the t value is 10.322 with a significance of p = 0.001(<0.05). The results of the second regression equation analysis show that the variables Perceived Usefulness and Perceived Ease of Use have a significant impact on the Attitude toward Using variable because the statistical value F count = 55.014 with a significance p = 0.001(<0.05). Keywords: Technology Acceptance Model, Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using.